1978
DOI: 10.1083/jcb.76.3.767
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-fracture observations of the lactating rat mammary gland. Membrane events during milk fat secretion.

Abstract: Membrane events during milk fat secretion were analyzed by freeze-fracture of the rat mammary gland. Two modes of milk fat secretion were observed: extrusion of fat droplets surrounded by a portion of the apical plasma membrane of the alveolar epithelial cells and, less frequently, release into the alveolar lumen of fat droplets contained in intracytoplasmic vacuoles. The extrusion process consists of two asynchronous events: clearing of membrane particles (probably including integral membrane proteins) and bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
1

Year Published

1980
1980
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 27 publications
1
10
1
Order By: Relevance
“…These data parallel the results of freeze-fracture electron microscopy from several laboratories which show that the fracture faces of MFGM are depleted of the intramembranous particles typically associated with integral proteins (27)(28)(29).…”
supporting
confidence: 87%
See 2 more Smart Citations
“…These data parallel the results of freeze-fracture electron microscopy from several laboratories which show that the fracture faces of MFGM are depleted of the intramembranous particles typically associated with integral proteins (27)(28)(29).…”
supporting
confidence: 87%
“…The results are at variance with some freeze-fracture studies which showed that MFGM and areas of the apical plasma membrane in close apposition with budding fat droplets are depleted of the intramembranous particles associated with integral membrane proteins (27)(28)(29). Since BTN comprises 20 -40% of the protein content of bovine MFGM (47,48), as an integral protein, it would be expected to give rise to identifiable particles on the fractured membrane halves.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The intracellular precursors of milk fat globules, milk secretory granules, arise as milk lipids inundate between the leaflets of the endoplasmic reticulum (ER) membrane, distending the leaflet facing the cytoplasm and causing primary droplets of accumulated lipid to bud off the ER (1,(3)(4)(5)(6). Milk secretory granules arise by the fusion of primary lipid droplets and are thus enveloped in a monolayer of phospholipids from the cytoplasmic leaflet of the ER membrane, as are all other lipid droplets (7)(8)(9)(10)(11)(12)(13)(14)(15). However, in contrast to all other lipid droplets, milk secretory granules are transported to the cell surface where they are pinched off into the alveolar space entirely surrounded in a layer of plasma membrane (2,(16)(17)(18).…”
mentioning
confidence: 99%
“…Major differences in protein composition were noted. However, fat globule membrane may not have the same composition as the apical plasma membrane and the secretory vesicle fractions may have been enriched in immature vesicle membranes (Peixoto de Menezes and Pinto da Silva 1978;Mather and Keenan 1983;Mather 1987). Well characterised fractions of apical plasma membrane and mature secretory vesicle membrane will be needed to resolve these issues.…”
Section: Discussionmentioning
confidence: 99%